China's new Red Guards the return of radicalism and the rebirth of Mao Zedong - Blanchette, Jude (Oxford University Press, 2019)
"As Jude Blanchette details in China's New Red Guards, two worrying trends in contemporary China point to Maoism's revival. First, an increasingly popular hard-edged form of nationalism that is reflexively anti-Western has taken root. The second is an unapologetic embrace of extreme authoritarianism that draws inspiration from the Maoist era. China's assertive stance in the South China Sea and anti-Japanese rhetoric represents the former, and the massive crackdown on liberal thought since Xi Jinping assumed the presidency represents the latter. The result is plain to see: a more authoritarian and more militaristic China. Blanchette goes further than this, though, arguing that what we're seeing is a full-fledged Maoist revival. He centers his story around a cast of nationalist intellectuals and activists who have helped unleash a wave of populist enthusiasm and nostalgia for the Great Helmsman's policies. That, combined with Xi's quick implementation of a range of authoritarian policies, suggests that the Maoist revival is neither epiphenomenal nor a passing fad. The ramifications, Blanchette suggests, are clear: those in the West who have been predicting waves of democratization and liberalization are living in a dream world, blithely unaware of either the Communist Party's commitment to authoritarianism or the degree of its residual veneration for the CCP's founding leaders. In sum, China's New Red Guards not only will reshape our understanding of the political forces driving contemporary China, it also demonstrates how ideologies can survive and prosper despite pervasive rumors of their demise"--